PENGEMBANGAN MODEL INSTRUMEN EVALUASI MENGGUNAKAN APLIKASI KAHOOT PADA PEMBELAJARAN EKONOMI - Muh. Fahrurrozi; Siti Nur Laili Rahmawati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2021)
This study aims to determine how the development of evaluation instruments using the Kahoot application and the effectiveness of the evaluation instruments using the Kahoot application. This type of research is a development with a research design model using ADDIE, namely analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). The validation results from material experts get the final percentage of 83% with very feasible criteria. The results of the validation from the media expert obtained a final percentage of 86% with very feasible criteria. In the assessment of students, the final percentage was 82% with very good criteria. On the test results, students got an average of 80%. The validity of the test results obtained 14 valid and 16 invalid questions, the reliability obtained in multiple choice questions was 0.77 in the high reliability category and in 5 true or false questions it was 0.28 with the low reliability category.